Efficacy, safety, and dose‐dependence of the analgesic effects of opioid therapy for people with osteoarthritis: systematic review and meta‐analysis. Issue 6 (9th February 2022) - Abdel Shaheed, Christina; Awal, Wasim; Zhang, Geoffrey; Gilbert, Stephen E; Gallacher, Daniel; McLachlan, Andrew; Day, Richard O; Ferreira, Giovanni E; Jones, Caitlin MP; Ahedi, Harbeer; Tamrakar, Mamata; Blyth, Fiona M; et al.
Abstract: Objective: To evaluate the efficacy and safety of opioids for analgesic therapy for people with osteoarthritis. Study design: Systematic review and meta‐analysis of randomised, placebo‐controlled trials of opioid therapies for treating the pain of osteoarthritis. The primary outcome was medium term pain relief (six weeks to less than 12 months). Quality of evidence was assessed with GRADE criteria. Data sources: MEDLINE, EMBASE, the Cochrane Database of Systematic Reviews and Central Register of Controlled Trials, CINAHL, PsycINFO, AMED, and the WHO International Clinical Trials Registry; trials published to 31 October 2020. Data synthesis: We extracted pain, disability, health‐related quality of life, and adverse events data for 36 eligible trials (overall dose range: 10‒210 oral morphine milligram equivalents [MME] per day). Continuous pain and disability outcomes were converted to common 0–100‐point scales; changes of less than ten points were deemed to be very small effects. Differences in dichotomous outcomes were expressed as risk ratios. Data were pooled for meta‐analysis in random effects models. The evidence from 19 trials (8965 participants; dose range, 10–126 MME/day) for very small medium term pain relief (mean difference [MD], –4.59 points; 95% CI, –7.17 to –2.02 points) was low quality, as was that from 16 trials (6882 participants; dose range, 10–126 MME/day) for a very small effect on disability (MD, –4.15 points; 95% CI, –6.94 to –1.35 points). Opioid dose was not statistically significantly associated with either degree of pain relief or incidence of adverse events in a meta‐regression analysis. Evidence that opioid therapy increased the risk of adverse events (risk ratio, 1.43; 95% CI, 1.29‒1.59) was of very low quality. Conclusions: Opioid medications may provide very small pain and disability benefits for people with osteoarthritis, but may also increase the risk of adverse events. PROSPERO registration: CRD42019142813 (prospective).